Total Phenolic Content and in vitro Antioxidant Potentials of Ethanolic Stem Extracts of Three Viburnum Linn. Species - Prabhu, K.; Karar, P.K.; Hemalatha, S.; Ponnudurai , K. (Asian Journal of Chemistry, 2010)
The stems of Viburnum punctatum, Viburnum coriaceum and Viburnum erubescens were collected from Nilgiri Hills and Coimbatore, Tamilnadu and taxonomically authenticated. Herbaria of the species were submitted to the museum of the place of research studies. The samples were shade dried for a week. About 500 g of powdered samples were extracted with petroleum ether (60-80 ºC), benzene and 75 % (v/v) ethanol successively in a soxhlator one by one and followed by determination of percentage extractives. The extracts were qualitatively tested for different chemical constituents present. The ethanolic extracts were selected for further investigations, such as total phenolic content and in vitro antioxidant potential. It was revealed that all the three species exhibited a significant antioxidant potential against the reference compounds subjected and antioxidant potential among three species was ascending in series: V. coriaceum > V. punctatum > V. erubescens.